PRODUKTIVITAS BONGKAR CURAH KERING PANGAN GANDUM DI DERMAGA 005C PADA PT PELABUHAN INDONESIA II - Nursery Alfaridi S Nasution; Andry Yudha Pratama; Nuryadi Nuryadi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
PT Pelabuhan Indonesia II in Banten is one of the port businesses in Indonesia located in Banten province. The purpose of this study is to investigate and analyze the use and maintenance of Gantry Luffing Crane, the impact of unloading process of dry bulk in port 005c and the correlation of the used of Gantry Luffing Crane for productivity of dry bulk in PT Pelabuhan Indonesia II. Field research and document analysis were used as the methods of this study. T-test was used to analyze the data. The result of this study shows that there is positive impact utilization of Gantry Luffing Crane in productivity dry bulk of grain. It could be seen from the point of productivity that increase 1 point or 0.6 point. Based on the correlation coefficient (r) 0,770 there is strong relation of the used Gantry Luffing Crane in loading productivity of dry bulk of grain. The determinant coefficient was 59.3% which is the contribution of the use of gantry luffing crane to the rise and fall of unloading productivity of dry bulk food of 59.3% and the rest of 40.7% is the unexamined influence of other factors. From the result of hypothesis test known that t value < t table is 3,511 <1,684 <1,684. There is a significant influence between the usage of gantry luffing crane to productivity of dry bulk food at PT Pelabuhan Indonesia II in Banten.